Milk, Moo, or Man Made? - Cunningham, Jordan Elizabeth (URJ-UCCS: Undergraduate Research Journal at UCCS, 2016)
The production of food has progressed rapidly within the last several decades, due in part, to the advancements in the field of science. One branch that continues to evolve is the cloning of livestock. Cloning has been a significant part of the scientific world for many years and it remains a controversial issue today. Since the early 1990’s, animals have been cloned mainly for breeding purposes and mass production of milk. Livestock cloning has been given the seal of approval by the FDA. In fact, by FDA standards, human consumption of cloned milk and meat products is safe. The FDA is so positive that eating cloned animal products poses no risk to people that it does not even require that these food products to be labeled. Therein lies the controversy. There is not enough long term data to determine the health risks to those who eat cloned animal foods. Since the FDA does not regulate clear and truthful labeling on cloned meat or milk, consumers have no way of knowing if they are eating cloned or conventionally bred animal products. This paper will examine the issues of using cloned animal products in the food supply and the necessity of labeling these products for consumers.